A New Block Cipher Algorithm Using Magic Square of Order Five and Galois Field Arithmetic with Dynamic Size Block - Malik ALattar, Ibrahim; Monem S. Rahma, Abdul (International Journal of Interactive Mobile Technologies (iJIM), 2021)
This paper describes the development of encryption algorithms using the magic square of order 5 and Multi-level keys with the addition of Matrix keys to increase implementation speed and complexity. This work relied mainly on the magic sum and some equations that were added as an improvement on previous work. Multi-level keys were used for three different message sizes, and an additional key matrix with size 5×5 was used to add more complexity. The proposed work was performed using both GF(P) and GF(28). Results were compared with the MS3, they have been found good, with acceptable speed and high complexity where it was (P)9 × (256)16 in the first algorithm, (P)9 × (256)16 × 3 in the second algorithm, and (P)9 × (256)16 × 3 × (P)25 in the third algorithm, the complexity changed according to the chosen value of N randomness, in addition to speed, complexity, NIST calculations have been performed for texts and histogram calculations for different images were calculated and compared as well.